The Effect of Aerobic Exercise on the Oxidative Capacity of Skeletal Muscle Mitochondria in Mice with Impaired Glucose Tolerance - Dan Wang; Dong-Mou Jiang; Rong-Rong Yu; Lin-Lin Zhang; Yan-Zhong Liu; Jia-Xin Chen; Hai-Chun Chen; Yi-Ping Liu (Journal of Diabetes Research)
Background/Objective. Impaired glucose tolerance (IGT) is an intermediate metabolic state between normal and diabetes and shows insulin resistant (IR) which to be linked with mitochondria dysfunction. This study is aimed at investigating whether aerobic exercise increases Mfn2 to promote mitochondrial function and improve glucose tolerance and insulin sensitivity in mice with high-fat diet. Methods. Male C57BL/6J mice were randomly divided into six different experimental groups (8 animals/group): (1) normal group (NOR), (2) normal control group (NC), (3) normal + exercise group (NE), (4) IGT group (IGT), (5) IGT control group (IC), and (6) IGT+ exercise group (IE).The exercise group received aerobic exercise for 8 weeks. After the intervention, a blood glucose meter was used to detect the level of glucose tolerance in the mouse’s abdominal cavity; a biochemical kit was used to detect serum lipid metabolism indicators, malondialdehyde, and superoxide dismutase levels; the ELISA method was used to detect serum insulin and mouse gastrocnemius homogenate LDH, PDH, SDH, and CCO levels. Western blot method was used to detect the protein expression levels of NOX4, PGC-1α, and Mfn2 in the gastrocnemius muscle of mice. Results. (1) Mice with high-fat diet for 30 weeks showed impaired glucose tolerance, insulin resistance, and lipid metabolism disorders. The level of LDH, PDH, SDH, and CCO in the gastrocnemius homogenate of mice was reduced. The expressions of NOX4 protein were significantly upregulated, while the expressions of PGC-1α and Mfn2 proteins were significantly downregulated. (2) 8-week aerobic exercise improved the disorders of glucose and lipid metabolism in IGT mice and increased homogenized LDH, PDH, SDH, and CCO levels, and the expressions of NOX4, PGC-1α, and Mfn2 proteins in the gastrocnemius muscle of mice were reversed. It is speculated that aerobic exercise can accelerate energy metabolism. Conclusion. (1) C57BL/6 mice were fed high fat for 30 weeks and successfully constructed a mouse model of reduced diabetes; the mice with reduced diabetes have impaired glucose tolerance, insulin resistance, and lipid metabolism disorders; (2) 8 weeks of aerobic exercise improve glucose tolerance, reduce glucose tolerance in mice, reduce insulin resistance, improve lipid metabolism disorders, and reduce oxidative stress; (3) 8-week aerobic exercise reduces skeletal muscle NOX4 expression and increases glucose tolerance; reduces the expression of LDH, PDH, SDH, and CCO in mouse skeletal muscle; increases the expression level of mitochondrial fusion protein 2 and PGC-1α; improves glucose tolerance; reduces energy metabolism of mouse skeletal muscle; reduces oxidative stress; and reduces insulin resistance. It is speculated that aerobic exercise can accelerate energy metabolism. This process may involve two aspects: firstly, increase the expression level of oxidative metabolism enzymes and promote the tricarboxylic acid cycle; secondly, increase the expression of Mfn2 and accelerate mitochondria fission or fusion to regulate energy metabolism, thereby reducing oxidative stress and insulin resistance.